Genetic diversity and agronomic morphological characteristics of 22 hybrid purple sweet corn genotypes - AGUNG TRIPUTRA TODINGRANTE; ARYA WIDURA RITONGA; SITI MARWIYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Todingrante AT, Ritonga AW, Marwiyah S. 2025. Genetic diversity and agronomic morphological characteristics of 22 hybrid purple sweet corn genotypes. Biodiversitas 26: 4124-4136. Purple sweet corn (Zea mays var. saccharata) is a nutritionally valuable crop known for its high anthocyanin content, which functions as a potent antioxidant. This study aimed to assess the genetic diversity and agronomic performance of 22 hybrid genotypes of purple sweet corn developed by Institut Pertanian Bogor. Field trials were conducted at the Pasir Kuda Experimental Station using a Randomized Complete Block Design (RCBD) with three replications. Eighteen quantitative and fifteen qualitative traits were evaluated to estimate genetic variability, heritability, and phenotypic expression. Analysis of variance indicated significant genotypic differences for the majority of traits. Broad-sense heritability estimates ranged from 8.24% (leaf width) to 96.99% (silking date), with high heritability observed for ear diameter (57.08%), ear weight with husk (66.40%), and Productivity (67.68%). The genotypic and phenotypic coefficients of variation revealed substantial genetic diversity across genotypes. Correlation analysis demonstrated that ear weight with husk (r = 0.68) and ear weight without husk exhibited strong and significant positive correlations with overall yield, highlighting their importance as effective selection criteria in breeding programs. Additional yield-contributing traits such as ear length, ear diameter, and number of kernel rows also showed positive associations with productivity, reinforcing their utility in selecting superior genotypes. Cluster analysis grouped the genotypes based on morphological and agronomic similarities. Genotype G19 showed exceptional performance, with a high yield (18.55 tons ha?¹) and deep kernel pigmentation, making it a promising candidate for future breeding. These results provide valuable insights for developing high-yielding, anthocyanin rich purple sweet corn cultivars with enhanced agronomic performance and nutritional quality.